Infertile Egg Powder Improves Nutrient Digestibility, Digestive Organ Development, and Performance of Broiler Chickens - Suprayogi, Wara Pratitis Sabar; Ratriyanto, Adi; Irawan, Agung (Buletin Peternakan, 2025)
This research investigated the effects of infertile egg powder (IEP) supplementation in the diets of broiler chickens on nutrient digestibility, digestive tract development, and performance. A total of 196 one-day-old male broiler chickens were randomized into four treatments differing in IEP levels, each with seven replicates of seven birds. The treatments were: 100% basal diet as a control (CON), 96% CON + 4% IEP (IEP4), 94% CON + 6% IEP (IEP6), and 92% CON + 8% IEP (IEP8). The observed variables included growth performance, nutrient digestibility, and digestive organ development. The results showed that dietary IEP enhanced the digestibility of dry matter, crude protein, ether extract, and crude ash (p<0.05), most noticeably in the IEP6 and IEP8 groups. However, IEP did not affect crude fiber and nitrogen-free extract digestibility. The birds consuming diets with IEP had heavier and more prolonged (p<0.05) duodenum, jejunum, ileum, and whole small intestines compared to the birds fed the CON diet. Dietary IEP also improved liver and gizzard weight (p<0.05). Feeding IEP did not affect feed intake but increased (p<0.05) crude protein and metabolizable energy intake, leading to an increase (p<0.05) of daily weight gain and concomitantly decreased (p<0.05) feed conversion ratio of the IEP groups. To conclude, IEP from hatchery had a positive response on the improved nutrient digestibility, digestive tract development, and performance of broiler chickens, and therefore, it can be used as a feed ingredient for broiler chickens.